Subtract: (3b−2c)−(6c+2b)−(b+c)

(
3
𝑏

2
𝑐
)

(
6
𝑐
+
2
𝑏
)

(
𝑏
+
𝑐
)
.(1 point)...

1 answer

To subtract the expressions, we can follow these steps:

  1. Distribute the negative signs inside each set of parentheses.
  2. Combine like terms.

Starting with the expression:

\[ (3b - 2c) - (6c + 2b) - (b + c) \]

First, distribute the negative signs:

\[ 3b - 2c - 6c - 2b - b - c \]

Now, combine like terms. First, combine the \(b\) terms:

\[ 3b - 2b - b = (3 - 2 - 1)b = 0b = 0 \]

Now, combine the \(c\) terms:

\[ -2c - 6c - c = (-2 - 6 - 1)c = -9c \]

Now, putting it all together, we have:

\[ 0 - 9c = -9c \]

Thus, the final result is:

\[ \boxed{-9c} \]